CORPORATE SOCIAL RESPONSIBILITY IN INDIAN BANKING INDUSTRY: STUDY ON ATTEMPTS OF HDFC BANK - Nidhi (International Journal of Research -GRANTHAALAYAH, 2016)
This paper is the study about the Corporate Social Responsibilities of the banking industry in India. Social Responsibility of business refers to what a business does over and above the statutory requirement for the benefit of the society. The word “responsibility” emphasizes that the business has some moral obligations towards the society. Corporate Social Responsibility also called Corporate Conscience or Responsible Business is a form of corporate self-regulation integrated into a business model. The paper is based on secondary data. Now-a-days CSR has been assuming greater importance in the corporate world including financial institutions and banking sector. Banks and other financial institutions start promoting environment friendly and socially responsible lending and investment practices. The paper consists of key areas of 6 banks and a case study on HDFC Bank.